Evaluation of flow, pH and buffer capacity of saliva in the gestational and post-breastfeeding period: a prospective case-control study (Brazilian Journal of Health Research, 2022)
Introduction: There is still divergence in the literature about salivary changes during the gestational period. Objectives: To evaluate the flow, pH and buffer capacity of the saliva of women in the gestational and postpartum period and compare it with non-pregnant women. Methods: The prospective case-control study with convenience sample between pregnant (P) and non-pregnant women (NP). The stimulated collection was performed in the morning during gestation and powder-delivery. Data were analyzed by the Shapiro-Wilk, t-Student, Mann-Whitney and Friedman tests (p 0.05). However, the saliva buffer capacity increased postpartum (p
Keywords: Pregnant women; Postpartum period; Saliva; Secretory rate; Acidity